Highly Shrinkable Objects as Obtained from 4D Printing. Issue 1 (13th October 2021) - Chalissery, Dilip; Schönfeld, Dennis; Walter, Mario; Shklyar, Inga; Andrae, Heiko; Schwörer, Christoph; Amann, Tobias; Weisheit, Linda; Pretsch, Thorsten
Abstract: 4D printing of shape memory polymers enables the production of thermoresponsive objects. In this contribution, a facile printing strategy is followed for an in‐house synthesized thermoplastic poly(ether urethane). Processing by means of fused filament fabrication, in which the difference between nozzle temperature and material‐specific glass transition temperature of the polymer is kept as low as possible, allows to obtain highly shrinkable objects whose shape and thermoresponsiveness can be precisely controlled. The effectiveness of the method also applies to the printing material polylactic acid. One possible application lies in highly shrinkable objects for assembly purposes. As proof‐of‐concept, lightweight hands‐free door openers for healthcare applications are functionally simulated and developed. Once printed, such devices shrink when heated to fit on door handles, allowing an easy assembly. At the end‐of‐use, a heating‐initiated disassembling and mechanical recycling are proposed. In perspective, a reuse of the materials in 4D printing can contribute to the emergence of a circular economy for such highly functional materials. Abstract : A simple 4D printing strategy is presented to realize heat‐shrinkable objects after fused filament fabrication. Distinct 4D effects enable assembly of hands‐free door openers from a self‐synthesized thermoplastic polyurethane or commercially available polylactic acid. The new approach can contribute to counteract the spread of smear infections and the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2).